(untitled) (International Journal of Engineering and Computer Science, 2017)
Now a day’s data protection is major issues in the cloud.As cloud computing becomes more n more popular, data outsourcing is additionally getting accumulated in large quantity. To provide protection to the privacy of sensitive data, the data needs to be get encrypted before it outsourced . However, this process makes less data utilization. to resolve the above problem the traditional cryptographic techniques provides effective search on the cloud data using keywords only but they have some drawback or limitations like they support only Boolean search techniques. Also, there results are irrelevant, not so accurate because of these techniques doesn’t work on file contents. This creates difficulty level in retrieving the document. Firstly user who doesn’t have any knowledge about encrypted cloud data, have to go through every retrieved file to get the more relevant file, also user will get all the files which are related to queried keywords which increases network traffic. So to overcome all above the drawbacks of existing traditional system we provide an efficient solution using ECC algorithm which will provide security to sensitive data and increases performance. The mining algorithm provides the ranked search which will enhance the usability of the system and returns the most relevant data with help of keyword frequency